Geographic accessibility to primary care providers: Comparing rural and urban areas in Southwestern Ontario - Shah, Tayyab I.; Clark, Andrew F.; Seabrook, Jamie A.; Sibbald, Shannon; Gilliland, Jason A. (The Canadian geographer, 2020)
This research examines geographical accessibility to primary care providers (PCPs) across urban and rural areas of Southwestern Ontario and examines variations in the distribution of PCPs in relation to the senior population (aged 65 years and older). Information about PCP practices was provided by the HealthForceOntario Marketing and Recruitment Agency. Population data were obtained from the 2016 Census of Canada. To calculate scores for accessibility to PCPs (i.e., PCPs/10,000 population), we applied the enhanced 2‐step floating catchment area method with distance decay effect within a global service catchment of 30‐minute drive time. A geospatial mapping approach revealed disparities in the distribution of PCPs with a pattern of higher spatial accessibility in or around major urban areas in Southwestern Ontario. Comparative analyses were performed in association with the seniors’ population to identify how accessibility scores were mismatched with the population needs. The outcome of this study will assist researchers and health service planners to better understand the distribution of existing PCPs to address inequalities, particularly in rural areas. Key Messages Southwestern Ontario has slightly better geographic accessibility to primary care providers than the provincial average, but there remain areas with provider shortages. Primary care provider distribution is unequal across the urban‐rural continuum, with lowest accessibility in rural and small population centres within the Census Metropolitan Area. There is a mismatch between the distribution of primary care providers and high proportions of seniors, necessitating many seniors to travel long distances to access health care. L'accessibilité géographique aux services de soins primaires: une comparaison entre les secteurs ruraux et urbains dans le sud‐ouest de l’Ontario La présente recherche étudie l'accessibilité géographique des populations aux dispensateurs de soins primaires (DSP) dans les secteurs ruraux et urbains du sud‐ouest de l'Ontario. Il s'agit aussi d'analyser les écarts dans la répartition des DSP par rapport à la population âgée (65 ans et plus). Sur le plan méthodologique, les informations concernant les pratiques des DSP ont été fournies par l'Agence de promotion et de recrutement ProfessionsSantéOntario. Pour leur part, les données sur la population proviennent du Recensement canadien de 2016. De plus, pour calculer les indices d'accessibilité aux DSP (c.‐à‐d., les DSP par population de 10 000), nous avons appliqué la méthode améliorée de zones de captage flottante en deux étapes avec effet de désintégration en fonction de la distance à l'intérieur d'un rayon global de 30 minutes en voiture. Ainsi, une technique de cartographie géospatiale a révélé des écarts dans la distribution des DSP avec un schéma spatial de haute accessibilité dans les principaux secteurs urbains du sud‐ouest de l'Ontario ou à proximité de ceux‐ci. En complément, des analyses comparatives ont été effectuées relativement à la population âgée dans le but de déterminer la façon dont les indices d'accessibilité étaient déphasés par rapport aux besoins de la population. Les résultats de la présente étude aideront les chercheurs et les planificateurs de soins de santé en Ontario à mieux comprendre la répartition des DSP existants afin de travailler à réduire les écarts, notamment dans les secteurs ruraux.